Metal‐Catalyzed Remote Functionalization of ω‐Ene Unsaturated Ethers: Towards Functionalized Vinyl Species. Issue 27 (1st June 2018) - Ho, Guo‐Ming; Judkele, Lina; Bruffaerts, Jeffrey; Marek, Ilan
Abstract: The combined ruthenium‐catalyzed chain walking with the nickel‐catalyzed cross‐coupling reaction of ω‐alkenyl ethers provide a unique entry to functionalized vinyl species. This transformation illustrates the power and flexibility of remote functionalization by demonstrating the compatibility of two independent reactions involving unrelated sites. Abstract : Walking a tightrope : The combined ruthenium‐catalyzed chain walking with the nickel‐catalyzed cross‐coupling reaction of ω‐alkenyl ethers provide a unique entry to functionalized vinyl species. This transformation illustrates the power and flexibility of remote functionalization by demonstrating the compatibility of two independent reactions involving unrelated sites.